Investigação dos impactos da lesão medular traumática na estrutura neuroanatômica de áreas corticais sensoriomotoras - Dyonísio, Gabriela (2019)
The loss of motor control is one of the most debilitating consequences of the spinal cord injury. Partial or complete disruption of the sensory and motor pathways render the individual unable to walk and perform various other activities. The occurrence of spontaneous sensorimotor cortical reorganization immediately after injury and continuously over time may occur in specific areas, as well as in the entire cerebral cortex. Understanding the complex interaction between anatomical, functional, and cortical reorganization induced by spinal cord injury, as well as defining its effects, is crucial to establish proper rehabilitation protocols. Structural magnetic resonance images were obtained to explore morphological changes in the Gray Matter (GM) and White Matter (WM) in the cerebral cortex of individuals with thoracic Spinal Cord Injury (SCI) and compared with images obtained from a group of volunteers without injury (NSCI)). Intergroup comparison was performed considering the time after the injury. Global evaluation of the brain did not detect changes in the total volume of GM. Volumetric differences in cortical GM were found in the pre-central gyrus and lower pre-central sulcus. The variation observed in the pre-central gyrus occurred in the left hemisphere, responsible for motor control of the right lower limb, which is compatible with the dominance of the volunteers of both groups (right-handed). The findings provide evidence that post-injury time did not have a considerable influence on the overall volumetric encephalic GM. However, changes in specific regions associated with motor control of areas below the lesion were evidenced in this study.